Os saberes mobilizados pelos professores alfabetizadores no processo de aprendizagem dos alunos ingressos no Ensino Fundamental I - Almeida, Patricia Melo Silva de (Universidade Federal de São Carlos, 2020)
The present study aimed to analyze the knowledge of pedagogical practice that literacy teachers mobilize in the process of inserting students in elementary school I. As specific objectives the research sought: to understand the experiences, challenges and proposals developed in this field of action; address the perception of literacy teachers in the face of this process; analyze the approximations and distances between the legal documents and the effectiveness of the proposal. The methodological procedures adopted were of a qualitative nature, carried out through a preliminary survey in the CAPES Theses and Dissertations Catalog (36) and in the UFSCar Thesis and Dissertations Repository website, totaling eleven researches analyzed; and, subsequently, the application of questionnaires, involving twelve literacy teachers working in the first year of elementary school, in São Carlos- SP . The theoretical framework that supported the study was supported by authors such as Tardif (2000, 2002, 2013) and Nóvoa (2017, 2019a, 2019b), for the discussion of professional knowledge and Soares (2004, 2005, 2017) for the discussion literacy. Among the results we can point out that disciplinary and curricular knowledge, coming from training courses and experiential knowledge, resulting from professional practice, are the sources that teachers most mobilize to teach, based on theoretical currents of various areas of knowledge, in a committed and conscious way, focused on the role of mediation and customer diversity. The data also reveal a critical and lack of chance of public policies and the lack of monitoring, training and support of EMS in relation to the demands presented by students, teachers, families.
The knowledge mobilized by literacy teachers in the learning process of students enrolled in Elementary School I
Keywords: Alfabetização; Professores alfabetizadores; Saberes profissionais; Ensino fundamental I; Literacy; Literacy teachers; Professional knowledge; Elementary school; CIENCIAS HUMANAS::EDUCACAO